Correlation of Degree between Grip Strength and Back Muscle Strength in Sports Education Students - Saputro, Deny Pradana; Adila, Fansah; Rahmatullah, Muhammad Imam; Ndayisenga, Japhet; Yulianto, Wahyu Wibowo Eko; Subekti, Nur (Universitas Negeri Surabaya, 2026)
Purpose: This research aimed to examine the degree and direction of the relationship between handgrip strength and back muscle strength among Physical Education students. Materials and Methods: The study utilized a non-experimental quantitative design with a cross-sectional correlational approach. It involved 38 Physical Education students (mean age= 20.42 ± 0.72 years) who had previously undergone injury screening. Handgrip strength was measured using a handgrip dynamometer, while back muscle strength was assessed with a back dynamometer. Data analysis included normality and linearity tests, followed by Pearson product-moment correlation. Result: The results revealed a positive and significant correlation between handgrip strength and back muscle strength (r = 0.839, 95% CI: 0.71–0.91, p < 0.001). Handgrip strength explained approximately 70.4% of the variance in back muscle strength, indicating substantial, but incomplete, shared variance with back muscle strength. Conclusion: These findings suggest that while there is an association between grip strength and back muscle strength, handgrip strength may serve as a practical screening indicator, but not a standalone substitute for direct back strength assessment. Future research is recommended to include a larger sample, employ a longitudinal design, and incorporate additional muscle-strength variables to improve the generalizability of the findings.